Solid-Phase Extraction and GC/MS Confirmation of Heroin Abuse in Urine - Mahmoud A. Alabdalla (Yanbu Journal of Engineering and Science)
A method for the analysis of urine for the heroin abuse is described. The analytical procedure uses solid-phase extraction (SPE), gas chromatography/mass spectrometry (GC/MS). It allows extraction, derivatization and analysis of 6-MAM and Morphine from urine. After solid-phase extraction was complete, the eluate was selectively derivatized with N-Methyltrimethylsilyltrifluoroacetamide (MSTFA). Analysis was performed using a GC/MS system operating in full scan mode. The mass spectrum of the derivatized metabolites was searched manually against reference libraries for positive identification and the retention time checked against that of the standard. This procedure has increased both the amount and the reliability of information given to analyst. The system has been in routine operation processing 100-150 urine samples per week. The results of the analysis of standard reference material and actual samples are presented and discussed. The developed method is sensitive enough to assess relevant 6-MAM and morphine levels in urine for forensic investigations.